2017
DOI: 10.1007/s11079-017-9457-9
|View full text |Cite
|
Sign up to set email alerts
|

On the Suitability of Alternative Competitiveness Indicators for Explaining Real Exports of Advanced Economies

Abstract: Reproduction permitted only if source is stated.ISBN 978-3-95729-299-5 (Printversion) Non-technical summary Research QuestionReal exports are commonly specified as depending on an indicator of price competitiveness and on a measure of foreign activity. It is unclear, however, which of the available indicators of price competitiveness is most closely connected to a country's export performance. Since the question of indicator suitability cannot be answered purely on conceptual grounds, we address it empiricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The conceptual model of the MCI presented in this work is adapted from Delgado-Márquez and García-Velasco (2018), Fischer et al (2018), Terzi c (2017), Ezell andAtkinson (2011), Lall (1992), Abramovitz (1986), Faberberg (1994), Archibugi and Coco (2004), Tan and Tan (2014), Milenkovic et al (2016), Shaker and Zubalsky (2015) and Lall and Albaladejo (2003). Lall (1992) argues that at the country level, capabilities can be grouped under three broad headings: physical investment, human capital and technological effort.…”
Section: Manufacturing Composite Index Framework and Their Shortcomingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conceptual model of the MCI presented in this work is adapted from Delgado-Márquez and García-Velasco (2018), Fischer et al (2018), Terzi c (2017), Ezell andAtkinson (2011), Lall (1992), Abramovitz (1986), Faberberg (1994), Archibugi and Coco (2004), Tan and Tan (2014), Milenkovic et al (2016), Shaker and Zubalsky (2015) and Lall and Albaladejo (2003). Lall (1992) argues that at the country level, capabilities can be grouped under three broad headings: physical investment, human capital and technological effort.…”
Section: Manufacturing Composite Index Framework and Their Shortcomingsmentioning
confidence: 99%
“…The broad-based indicators include unit labor cost, deflators of sales and real exchange rates, weighted average of real GDP, aggregate imports of goods and services and volume of global trade. These broad-based indicators are suited well for measuring the competitiveness of countries (Fischer et al, 2018). The competitiveness of a country can also be measured by benchmarking their investments and achievements in the information and communication technologies sector (Milenkovic et al, 2016).…”
Section: Cr 302mentioning
confidence: 99%
“…Taking account of this argument, we develop a modified ULC measure at the sectoral level that better describes the competitive stance of each sector. The "embodied unit labor costs" (EULC) of a specific sector not only consider that sector's own ULC but also take account of the ULC incorporated in the intermediate goods delivered to this sector, and therefore are a weighted average of ULC 1 Different price-and cost-related REERs are, for example, compared in Marsh and Tokarick (1996), Chinn (2006), Ca'Zorzi and Schnatz (2007), Christodoulopoulou and Tkačevs (2014) and Fischer et al (2016). Usually it is found that neither competitiveness indicator clearly outperforms the other.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limited country coverage of the AMECO database, the number of countries decreases from 46 to 36. See, e.g.,Fischer et al (2018) for a comparison of various indicators of international price competitiveness.…”
mentioning
confidence: 99%